Proceedings of the 22nd International Academic Conference 2016
DOI: 10.20472/iac.2016.022.050
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Adoption of Proactive Environmental Strategies in Polish Companies

Abstract: Nowadays, many companies are under pressure to take care about the natural environment. However, companies differ from one to another because of their response to natural environment. For this reason companies implement different environmental strategies. The literature indicates a continuum range from passive to proactive strategies. The proactive strategies are typical for companies that voluntarily take measures to reduce their impact on the natural environment. The reasons for a lack of environmental proac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Employee psychological climate plays a key role in producing high organizational performance [42,43]. Some studies demonstrated that the main factor causing delays in organizational environmental improvement is how to create a sustainable organizational climate [44][45][46]. First of all, if employees are not responsible for the use of the company's energy and facilities, it is difficult for them to invest in green behaviors [47].…”
Section: Green Psychological Climate and Green Product Development Performancementioning
confidence: 99%
“…Employee psychological climate plays a key role in producing high organizational performance [42,43]. Some studies demonstrated that the main factor causing delays in organizational environmental improvement is how to create a sustainable organizational climate [44][45][46]. First of all, if employees are not responsible for the use of the company's energy and facilities, it is difficult for them to invest in green behaviors [47].…”
Section: Green Psychological Climate and Green Product Development Performancementioning
confidence: 99%
“…The green psychological climate is considered because employees’ perception of green climate positively affects employees’ pro-environmental behaviors (Dumont et al, 2017; Norton et al, 2017; Zhou et al, 2018). On the contrary, employees’ perception that organizational policies and procedures do not support environmental sustainability discourages employees’ engagement in pro-environmental behaviors and deteriorates firms’ green performance (Seroka-Stolka and Lukomska-Szarek, 2016; Zientara and Zamojska, 2018; Tuan, 2019; Wang et al, 2019). We suggest that managers can encourage employees to demonstrate OCBE by instilling a sense among employees that organizational policies and practices are eco-friendly.…”
Section: Introductionmentioning
confidence: 99%